Carbon impact assessment of bridge construction based on resilience theory - Zhou, Zhi Wu; Alcalà, Julián; Yepes, Víctor (Journal of Civil Engineering and Management, 2023)
The construction and management of large-scale projects have the characteristics of complexity, dynamic and offline, and how to evaluate it is a research problem accurately. This study addresses this question through multidisciplinary cross-applied research. The research analyses and optimizes the environmental impact of the construction stage of superlarge bridges by establishing a theoretical model system of environmental impact resilience. The analysis shows that industrialized construction can save 56.31% of materials compared with traditional construction but increase the consumption of machinery and personnel by 11.18%. Ultimately, environmental pollution can be significantly reduced. This study breaks through the difficulty of accurately evaluating discrete dynamic factors. It has realized the application of multidisciplinary research to solve management optimization and design problems in the elastic and dynamic changes of super-large bridges during construction. This research provides rich theoretical models and advanced analytics experience data for environmental resilience impacts and project resilience management models, laying a solid scientific foundation for dynamic control and sustainable development assessment of statically indeterminate structures in the future.